Familial Hypokalaemic Periodic Paralysis A Case Report - Majumder, Md Shafayet Hasan (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Familial hypokalaemic periodic paralysis is a relatively uncommon but potentially life-threatening clinical condition. If recognized and treated appropriately during the episode, patients recover without any clinical sequellae. Reported case presented with recurrent attack of flaccid paralysis of limbs precipitated by carbohydrate meal. Familial periodic paralysis was diagnosed by clinical evidence of flaccid paralysis with positive family history and proved by ECG changes, biochemical findings and hypokalaemia in the absence of other causes of hypokalaemia. The patient improved dramatically with potassium supplementation. Understanding of the illness requires going through recent advances both in electrophysiology and in molecular biology of channelopathies, especially calcium channel structures, functions and genes. Key words: periodic paralysis, hypokalaemia. DOI:10.3329/jbcps.v27i3.4295 J Bangladesh Coll Phys Surg 2009; 27: 166-168